(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Uttarakhand is currently one of the world’s fastest-developing tourism destinations. While the possibilities of tourism advancement in India by and large and the state of Uttarakhand specifically appear to be very encouraging, fears about the sustainability of the same develop. In the above context, this paper seeks to impact on Indian Tourism Development Practices of Sustainable Tools, with special reference to ROSE Kanda, Bageshwar, Uttarakhand, India.